Climate change impacts on water quantity and quality: Implications for agriculture - Ringler, Claudia (2015)
Claudia Ringler, IFPRI (with Tingju Zhu, Hua Xie & Mark Rosegrant and the IMPACT Food model team) Water Policy for Food Security UC Davis, October 5-6